Highlights of the Twelfth Emirates Diabetes and Endocrine (Virtual) Congress, 24–26 February 2022 - Salem A. Beshyah; Fauzia Rashid; Elamin Ibrahim Abdelgadir (Dubai Diabetes and Endocrinology Journal)
Backgrounds: The Twelfth Diabetes and Endocrine Virtual Congress (EDEC 2022) was held on 24–26 February 2022 due to the COVID pandemic. Objectives: We aimed to present highlights of the congress proceeding. Methods: Three rapporteurs prepared this congress report. They prepared assigned sections, reviewed the rest of the manuscript, and approved its final version. Conference Highlights: The conference contents over 3 days included a wide range of lectures by world-class experts and key opinion leaders on various topical subjects, endocrinology, diabetes care, and metabolism, in addition to original data from submitted abstracts. The virtual EDEC 2022 provided a comprehensive review of topical issues concerning clinical practice and research in diabetes, endocrinology, and metabolism. The clinical approach to managing a pituitary mass, contemporary management of acromegaly, and the challenging prolactin disorders, thyroid nodules, hyperparathyroidism, polycystic ovary, and premature ovarian failure were also discussed. On the diabetes side, emphasis on the cardiovascular outcomes, using newer agents when compelling indications exist, hypoglycemia, hypertension, and halting of chronic kidney disease progression were discussed. Other presentations considered type 1 diabetes care, the latest guidelines, role of technology in diabetes care, including telemedicine and some regional experiences. Use and abuse of testosterone were reviewed. The newer and future lipid-modifying therapies in adults and children were discussed. Conclusions: This EDEC 2022 session provided a comprehensive review of topical issues in clinical practice and research in diabetes, endocrinology, and metabolism.